2017
DOI: 10.21037/jtd.2017.08.140
|View full text |Cite
|
Sign up to set email alerts
|

Chest tube drainage versus needle aspiration for primary spontaneous pneumothorax: which is better?

Abstract: Background: Needle aspiration and chest tube drainages are two main treatments for primary spontaneous pneumothorax (PSP). However, the application of needle aspiration or chest tube drainages has not reached a consensus. The aim of this study is to compare the needle aspiration with chest tube drainages in patients suffering with PSP and therefore help offer suggestions for clinical practice. and risk ratio (RR) respectively, and each with 95% confidence intervals (CIs). We used the fixed effect or random eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
(50 reference statements)
0
7
1
2
Order By: Relevance
“…A recent Cochrane systematic review (2017) also reported a shorter hospital stay and a reduction of side effects after simple NA compared to chest tube drainage (CTD) . Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions . Thelle recently published a randomized controlled study of 127 patients with pneumothorax (79 PSP and 48 SSP) comparing NA with CTD .…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 82%
“…A recent Cochrane systematic review (2017) also reported a shorter hospital stay and a reduction of side effects after simple NA compared to chest tube drainage (CTD) . Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions . Thelle recently published a randomized controlled study of 127 patients with pneumothorax (79 PSP and 48 SSP) comparing NA with CTD .…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 82%
“…In PSP patients with a small pneumothorax (size ≤25%), the general consensus is that observation with O2 inhalation is most appropriate [6,7]. However, there is no clear guideline for PSP patients with a large pneumothorax (size >25), and variations exist in international guidelines and clinical practice [8,9]. These discrepancies arise from a lack of high-quality evidence obtained from a variety of prospective studies [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…NA and CTD were compared in two recent meta-analyses. 23,24 Both studies acknowledged that NA is associated with a shorter stay in hospital but the Cochrane analysis concludes that CTD had a higher immediate success rate, although there was little supporting evidence. Walker and Maskell point out in their editorial that, while NA is associated with fewer bed days and adverse events, it has an initial risk of failure rate of 50%.…”
Section: Discussionmentioning
confidence: 99%